Préconcentration sur Silice Chélatante Chargée en FeIII - Possibilités d'Application à l'Analyse du Catéchol et de ses Dérivés - Antoine A. Descombes; Werner Haerdi (CHIMIA)
Preconcentration of organic compounds on a iron(III)-loaded 8-hydroxyquinoline-silica chromatographic pre-column is described. The compounds tested include amino acids, phenol, catechol, resorcinol, hydroquinone, and some other aromatic dihydroxy species, of which only the ortho-dihydroxy compounds are retained by this metal-loaded silica. As a model, the effect of pH, ionic strength, and flow rate on the retention of catechol is discussed. – Acetic acid is used as the eluent. The effect of the acid concentration and flow rate on the efficiency of elution is also discussed. An application to the chromatography of some catecholamines is presented.